Pengaruh Parenting Education Pada Ibu Terhadap Pengetahuan dan Sikap Ibu Terhadap Balita Tentang Tumbuh Kembang - Siti Patimah; Dita Eka Mardiani (Syntax Corporation Indonesia, 2022)
The role of the family, especially the mother in raising children, is very important in determining the growth and development of children. In order for parents to be able to carry out their functions properly, parents need to understand the level of child development, assess the growth or development of children, and have a strong motivation to advance the growth and development of children. The results of the study on parenting education show that the skills of parents in carrying out the parenting function are still low Syakrani, 2010 the causes include the absence of parenting programs, low understanding and awareness of parents about the importance and influence of motherhood on children's growth and development, and lack of information about the importance of parenting. child care. Shochib, 2010 explains that the knowledge and attitudes of parents in providing parenting to their children are influenced by the lack of information about ways to achieve a healthy life which can lead to deviations in parenting patterns for children. This study aims to determine the effect of parenting education on mothers of infants under five on the knowledge and attitudes of mothers of infants under five about growth and development. The research method used in this study is a quasi-experimental one-group pretest-post test design. The population of this research is mothers of infants under five in the Cikalang Village, Tasikmalaya City. The subjects of this study were mothers of infants under the age of five in the Cikalang sub-district who were selected using the purposive sampling method. The sample selected as the respondent is determined based on the criteria. Total 70 0 people. univariate analysis to determine the frequency distribution. The results of the data normality test showed that the data distribution was not normal, so the bivariate test used the Wilcoxon test. The results of the study obtained knowledge of mothers of infants under five about growth and development of infants under five before parenting education, the highest level of mother knowledge was in the less category (67.1%), while after attending parenting education the mother's level of knowledge was in the medium category (60%) and the good category (40%). Prior to parenting education, the mother's attitude was mostly in the bad category (64.3%), while after attending parenting education the mother's attitude was mostly in the good category (87.1%). The results of the different test were known as the Asymp.Sig value. (2-tailed) of 0.000 <0.05, which means that H0 is rejected. It can be concluded that there is an influence of parenting education on the knowledge and attitudes of mothers of infants under five about the growth and development of infants under five.